2003
DOI: 10.1093/jn/133.10.3200
|View full text |Cite
|
Sign up to set email alerts
|

Total Fumonisins Are Reduced in Tortillas Using the Traditional Nixtamalization Method of Mayan Communities

Abstract: Fumonisin B1 (FB1) is a maize mycotoxin. In tortilla preparation, maize is treated with lime (nixtamalization), producing hydrolyzed FB1 (HFB1) due to loss of the tricarballylic acid side chains. This study determined the following: 1) whether nixtamalization by Mayan communities reduces total fumonisins, and 2) the steps in the process at which reduction occurs. Tortillas prepared by the traditional process contained FB1, FB2 and FB3 and their hydrolyzed counterparts. There were equimolar amounts of FB1 and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 13 publications
4
46
0
Order By: Relevance
“…As only spot urines were available, we measured urinary creatinine to adjust for expected variations in urinary volume and FB1 levels were still strongly correlated with maize consumption when expressed in this way. In addition, we measured only FB1 in this study, although the tortillas are likely to also contain FB2 and FB3 as well as the hydrolyzed forms of FB1, FB2, and FB3 following the process of nixtamalization (33). Future consideration of other urinary fumonisins would be of value both in terms of exposure assessment but also to explore the absorption of different fumonisins in exposed people.…”
Section: Discussionmentioning
confidence: 99%
“…As only spot urines were available, we measured urinary creatinine to adjust for expected variations in urinary volume and FB1 levels were still strongly correlated with maize consumption when expressed in this way. In addition, we measured only FB1 in this study, although the tortillas are likely to also contain FB2 and FB3 as well as the hydrolyzed forms of FB1, FB2, and FB3 following the process of nixtamalization (33). Future consideration of other urinary fumonisins would be of value both in terms of exposure assessment but also to explore the absorption of different fumonisins in exposed people.…”
Section: Discussionmentioning
confidence: 99%
“…Others found that the traditional nixtamalization method (ca. 400 g corn, 0.2 L lime solution (82 g CaO/L), 1.1 L water, 1008C, 105 min) used by the Mayan communities in Guatamala reduced total fumonisins (FB 1 and HFB 1 ) by 50% [94] and that the residual lime and washing water also contained 50% of the fumonisins initially present in the corn.…”
Section: Thermal Treatmentmentioning
confidence: 99%
“…Conversely, there are several studies on the FBs content in other traditional foods, such as tortillas, and polenta, typical maize-based products from Mexico and northern Italy, respectively (Stack, 1998;Dombrink-Kurtzman and Dvorak, 1999;De La Campa et al, 2004;Palencia et al, 2003).…”
Section: Introductionmentioning
confidence: 99%